E-COMMERCE MANAGEMENT STRUCTURE OF ENTERPRISE PRODUCTS (Marketing Journal, 2025)
This article analyzes the structure for effectively managing the sale of enterprise products through e -commerce in the context of the modern digital economy. The key components of the e -commerce system — including product placement on digital platforms, cu stomer interaction, order processing, payment, and delivery — are examined. The article also highlights the importance of automating and monitoring e - 407 commerce operations, their impact on business processes, and their role in improving efficiency. Based on flowcharts, graphs, and organizational models, an optimal electronic commerce system for enterprises is proposed. As a result, the paper substantiates the potential to expand product sales, promptly meet customer demands, and enhance market competitiveness.
Keywords: E-commerce; infrastructure; traffic; app; B2B; B2C; website; distribution; platform